Actions Of Parents In Keeping Children's Tooth And Mouth Cleanliness At The State Of Elementary School Of Mns Peureulak, Mutiara District, Pidie Regency - Rahmil Izzati; wirza (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
At the age of school children, the actions of parents are things that will be role models and imitated by their children. Therefore, parents must teach their children to start good habits. The results of interviews with 15 parents found that 10 parents rarely asked their children to brush their teeth before going to bed. This study aims to determine the actions of parents in maintaining dental and oral health with the status of dental and oral hygiene in students of SD Negeri Menasah Peureulak, Mutiara District, Pidie Regency. This type of research is descriptive, the data collection technique uses a questionnaire and PHP-M examination sheet. The population in this study amounted to 123 people and the sample in this study amounted to 55 parents and 55 students using the proportional stratified random sampling technique. Of the 55 students of SD Negeri Menasah Peureulak Mutiara, Pidie Regency, regarding the actions of parents in maintaining dental and oral hygiene of big children, they were in the less category, namely 30 parents (55%), while the status of dental and oral hygiene with the PHP-M examination was at in the bad category as many as 29 students (53%) and in the very bad category one student (2%).